THE EVALUATION OF THE INFLUENCE OF A POLITICAL FACTOR FOR ECONOMIC GROWTH IN UKRAINE - Stavytskyy, A.V; Zatonatska, T.G. (Ekonomika, 2010)
The article deals with the complex of economic-mathematical models applied for the investigation of the influence of some kinds of budget expenses on economic growth considering changes in the Ukrainian economic system over the last years. The main idea of the investigation is to analyze the effectiveness of budget expenditures under the political changes that took place in Ukraine in 2005–2009.p>